In situ simulation: detection of safety threats and teamwork training in a high risk emergency department. Issue 6 (20th December 2012) - Patterson, Mary D; Geis, Gary Lee; Falcone, Richard A; LeMaster, Thomas; Wears, Robert L
Abstract : Objective: Implement and demonstrate feasibility of in situ simulations to identify latent safety threats (LSTs) at a higher rate than lab-based training, and reinforce teamwork training in a paediatric emergency department (ED). Methods: Multidisciplinary healthcare providers responded to critical simulated patients in an urban ED during all shifts. Unannounced in situ simulations were limited to 10 min of simulation and 10 min of debriefing, and were video recorded. A standardised debriefing template was used to assess LSTs. The primary outcome measure was the number and type of LSTs identified during the simulations. Secondary measures included: participants' assessment of impact on patient care and value to participants. Blinded video review using a modified Anaesthetists Non-Technical Skills scale was used to assess team behaviours. Results: 218 healthcare providers responded to 90 in situ simulations conducted over 1 year. A total of 73 LSTs were identified; a rate of one every 1.2 simulations performed. In situ simulations were cancelled at a rate of 28% initially, but the cancellation rate decreased as training matured. Examples of threats identified include malfunctioning equipment and knowledge gaps concerning role responsibilities. 78% of participants rated the simulations as extremely valuable or valuable, while only 5% rated the simulation as having little or no value. Of those responding to a postsimulation survey, 77% reported little or no clinical impact. Video recordings did not indicate changes in non-technical skills during this time. Conclusions: In situ simulation is a practical method for the detection of LSTs and to reinforce team training behaviours. Embedding in situ simulation as a routine expectation positively affected operations and the safety climate in a high risk clinical setting.